Progress in nanoimprint wafer and mask systems for high volume semiconductor manufacturing - Murasato, Naoki; Arai, Tsuyoshi (SPIE, 2018)
Nanoimprint lithography manufacturing equipment utilizes a patterning technology that involves the field-by-field deposition and exposure of a low viscosity resist deposited by jetting technology onto the substrate. The patterned mask is lowered into the fluid which then quickly flows into the relief patterns in the mask by capillary action. Following this filling step, the resist is crosslinked under UV radiation, and then the mask is removed, leaving a patterned resist on the substrate. The technology faithfully reproduces patterns with a higher resolution and greater uniformity compared to those produced by photolithography equipment. Additionally, as this technology does not require an array of widediameter lenses and the expensive light sources necessary for advanced photolithography equipment, NIL equipment achieves a simpler, more compact design, allowing for multiple units to be clustered together for increased productivity. In this paper, we review the progress and status of the FPA-1200NZ2C wafer imprint system and FPA-1100NR2 mask replication system. To address high volume manufacturing concerns, an FPA-1200NZ2C four-station cluster tool is used in order to meet throughput and cost of ownership requirements (CoO). Throughputs of up to 90 wafers per hour were achieved by applying a multi-field dispense method. Mask life of up to 81 lots, using a contact test mask were demonstrated. A mix and match overlay of 3.4 nm has been demonstrated and a single machine overlay across the wafer was 2.5nm. There is Mask Replication criteria that are crucial to the success of a replication platform include image placement (IP) accuracy and critical dimension uniformity (CDU). Data is presented on both of these subjects. With respect to image placement, an IP accuracy (after removing correctables) of 0.8nm in X, 1.0nm in Y has been demonstrated.